The impact of endoscopic sinus surgery and aspirin desensitization on psychological burden in aspirin‐exacerbated respiratory disease. Issue 4 (1st December 2020) - Locke, Tran; Sweis, Auddie; Lin, Theodore; Sweis, Brian; Gleeson, Patrick; Kohanski, Michael; Adappa, Nithin; Palmer, James; Bosso, John
Abstract : Background: Aspirin‐exacerbated respiratory disease (AERD) is an aggressive inflammatory disorder of the upper and lower respiratory tract. Corticosteroids, leukotriene modifiers, endoscopic sinus surgery (ESS), aspirin (ASA) desensitization, and biological immunomodulators are currently used to treat the disorder. Objective: The objective of this study was to determine the psychosocial impact of ESS and ASA desensitization on AERD patients. Methods: All AERD patients who underwent complete ESS were divided into two cohorts based on ASA desensitization status. The psychosocial metrics of the SNOT‐22 were collected and analyzed at the following time points: pre‐operative, 1‐month, 3‐month, 6‐month, and 12‐month after ESS. Results: One hundred and eighty‐four AERD patients underwent ESS from November 2009 to November 2018. From this group, 130 patients underwent ASA desensitization (AD cohort) and 54 patients remained non‐desensitized (ND cohort). AD patients showed a significantly greater reduction in total SNOT‐22 scores over the study period compared to ND patients ( p = 0.0446). Analysis of SNOT‐22 psychosocial metrics showed a significantly greater improvement in patient productivity in the AD cohort when compared to the ND cohort ( p = 0.0214). Further, a sub‐group analysis accounting for subject attrition showed a significantly greater improvement in both productivity and concentration in AD patients when compared to the ND cohort (productivity: p = 0.0068; concentration: p = 0.0428). Conclusions: ESS followed by ASA desensitization decreases the overall psychosocial burden in AERD patients with a significant improvement in perceived productivity and concentration. This has significant implications given the psychosocial impact of chronic diseases.